Intended Reader Perception over Mrs. Bennet’s Character in Jane Austen’s Novel Pride and Prejudice - Aliki Aliki; Mery Balango; Adriansyah A. Katili (Jurnal Bahasa, Sastra, dan Budaya, 2023)
The portraits of women in literary works are very diverse. The reader has an important role  in interpreting issues and fenomena in the work through a response. To see the reader response, a literary reception approach is used, an approach that involves the reader as the main object. This study aims to reveal intended reader perceptions of Mrs. Bennet's character in Jane Austen's novel Pride and Prejudice by using literary reception theory in a synchronous method. A qualitative research method was applied by collecting primary data from participants in the form of responses from the intended reader in the different  period, using Jauss's literary reception approach. The results show that the readers' responses to Mrs. Bennet's character, whether as a woman, wife, or mother, were quite diverse. It also shows that gender, religion, environment, some particular traditions, space, and time are things that greatly influence the reader's response. Then it shows the intended reader's reception towards Mrs. Bennet's character is shaped by experience, the horizon of expectation, aesthetic distance, and the space and time of the reader in the different period.